Motivasi Intrinsik Terhadap Kinerja Pegawai Pada Bagian Organisasi dan Kepegawaian Sekretariat Daerah Kabupaten Konawe: Intrinsic Motivation on Employee Performance in the Organization and Personnel Section of the Konawe Regency Regional Secretariat - Edy Tadung; Andi Muh. Dzul Fadli; Dian Tri Wahyuni (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2022)
This article examines the relationship between intrinsic motivation and work performance of civil servants as well as factors influencing such a motivation. The study case was carried out in the Organisation and Staffing Section of the Konawe District by using a descriptive qualitative approach. Research findings show that from the perspective of work achievement, intrinsic motivation is not optimally understood as the employees still awaited their employer’s guidance to carry out certain jobs or tasks. In regards to the aspect of work responsibility, work disciplines are still weak, as proven by some employees disobeying office regulations. However, from rewarding side, the provision of rewards is quite good as the employer appreciated those who performed best in executing office tasks. Factors that contribute considerably to intrinsic motivation are passion to succeed, hope, and rewards. For those who performed less well in their jobs, technical guidance and training are necessary to improve their work performance.